Market systems change rubric - and Loveridge, Donna (Oxford Policy Management, 2022)
This systems change rubric describes different performance levels according to various systems elements, such as policy (formal rules), practices and relationships and connections. Programmes can use the rubric to assess the performance of systems to help decide where and how to intervene, or during and post-implementation to conduct progress assessments, and assess the effectiveness of interventions and type, breadth and depth of systems change. Each performance level description highlights the type of data and information that needs to be collected. One analysis is completed, users can compare this to the performance descriptions to see which level best matches the analysis. This helps programmes draw conclusions about systems changes. The rubric was developed in 2020 and tested in 2021 and builds on systems change thinking and frameworks from two previous FSG publications. It can be used as: pre-intervention to conduct an assessment during an intervention to conduct progress assessments and reflect on the effectiveness of interventions to change systems and inform decision making post intervention to make judgements about whether interventions were valuable given the resources, time and effort spent Useful for: Implementation managers to determine the effectiveness of interventions, as well as by Monitoring, Evaluation and Learning (MEL) teams to track progress against expected outcomes.